Survival Across the Fitness-Stress Continuum Under the Ecological Stress Theory of Aging: Caloric Restriction and Ionizing Radiation - Peter A. Parsons (SAGE Publishing, 2010)
Free living organisms typically occur in harsh environments challenged by abiotic stresses of varying intensities. Taking ionizing radiation and caloric restriction as examples, environmental variation from benign to extreme gives a fitness-stress continuum where energetic efficiency, a measure of fitness, is inversely related to stress level. Hormesis occurs in benign regions for these examples. In contrast aging emphasizes survival towards the limits of survival under accumulating stress from Reactive Oxygen Species, ROS. An energetic evolutionary approach underlies an ecological aging theory based principally upon survival, which incorporates hormesis. Multiple environmental agents contributing to hormesis should be considered by those attempting to improve the quality of life by delaying the onset of senescence, so enhancing survival. Caloric restriction has wider acceptance in this process than ionizing radiation.